Effective Defensive Strategies at the Ruck Contest in Rugby Union - Wheeler, K.; Mills, D.; Lyons, K.; Harrinton, W. (International Journal of Sports Science and Coaching, 2013)
Performance analysis examined the association between defensive strategies and ruck outcomes in rugby union. Defensive tactics at the ruck contest were coded (n = 8563) during 60 games of the 2011 Super Rugby competition. Variables described attacking width, territory gained by the attack, defensive strategy used at the ruck, and ruck outcome. Chi-squared analysis showed that both early counter ruck (competing for the ball without hands) and jackal (competing for the ball with hands) were effective at turning over possession of the ball behind the advantage line (60% and 39% of turnovers, respectively). Early counter ruck was also effective at turning over possession when the ruck contest occurred in the wide attacking channels (18% of turnovers) whilst a jackal was used at ruck contests occurring in central field areas (13% of turnover). Late counter ruck was a poor strategy and was likely to concede penalties without an association with turnovers.